2022
DOI: 10.3390/bioengineering9070277
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Microleakage at the Implant-Abutment Interface: An In Vitro Study

Abstract: The objective of this study is to evaluate, in vitro, the microleakage of bacteria of 3 different implant connections for a period of 14 days. 60 dental implants (AoN) (n = 20) were distinguished into three groups, accordingly to the type of connection: External Hexagon (EH), Internal Hexagon (IH), and Cone Morse (CM) connection. All implants were inserted and fixed on sterile special vinyl support. Ten fixtures for each group were inoculated in the internal platform with 1.0 μL of Streptococcus oralis (SO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This is in agreement with previous studies [7,8]; indeed, the few studies that have reported on bacterial contamination at the abutment-prosthesis coupling level demonstrate either an absence of a complete bacterial seal or no bacterial infiltration into and from this coupling. One of these studies reported an in vitro investigation of the microleakage of bacteria in three different implant connections for a period of 14 days [36]; in this case, 60 dental implants were distinguished into three groups, according to the type of connection: external hexagon, internal hexagon, and conometric connection. All implants were immersed in a bacterial suspension into the surrounding solution.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies [7,8]; indeed, the few studies that have reported on bacterial contamination at the abutment-prosthesis coupling level demonstrate either an absence of a complete bacterial seal or no bacterial infiltration into and from this coupling. One of these studies reported an in vitro investigation of the microleakage of bacteria in three different implant connections for a period of 14 days [36]; in this case, 60 dental implants were distinguished into three groups, according to the type of connection: external hexagon, internal hexagon, and conometric connection. All implants were immersed in a bacterial suspension into the surrounding solution.…”
Section: Discussionmentioning
confidence: 99%
“…Two-piece dental implants, consisting of an implant body and a transmucosal part (abutment) that the dental crown is mounted on, are widely used for dental restoration due to their flexibility in prosthetic angle, based on the abutment selected (angled or straight) . However, a disadvantage to the two-piece dental implant can be the existence of poor sealing along the implant body-abutment interface, providing a potential site for colonization of bacterial pathogens consisting of oral pathogens like Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, or other pathogens, for example, Staphylococcus aureus and Pseudomonas aeruginosa transferred from anterior nares or skin. , The literature has reported the migration of bacteria into the internal part of the bone implant through such a microgap and micromovement of the implant-abutment, causing interference with the health of the preimplant tissue, inflammation, and bone loss. , To avoid dental implant loss due to infection and inflammation response, some antibiotics like prophylaxis were prescribed to a patient immediately after dental surgery or amoxicillin 1 h before dental surgery. , Therefore, the development of new biomaterials without containing any toxic ions and modifying their surface properties can prevent an increased number of antibiotic-resistant bacteria due to the routine consumption of antibiotics before or after surgery. Sarac et al demonstrated that titanium-based metallic glasses (MGs) outperform the gold-standard Ti–6Al–4V when used as dental implants. , Yet, the development of titanium-based metallic glasses devoid of potentially toxic metals is imperative to mitigate any potential inflammatory reactions within the body .…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 The literature has reported the migration of bacteria into the internal part of the bone implant through such a microgap and micromovement of the implant-abutment, causing interference with the health of the preimplant tissue, inflammation, and bone loss. 10 , 11 To avoid dental implant loss due to infection and inflammation response, some antibiotics like prophylaxis were prescribed to a patient immediately after dental surgery or amoxicillin 1 h before dental surgery. 12 , 13 Therefore, the development of new biomaterials without containing any toxic ions and modifying their surface properties can prevent an increased number of antibiotic-resistant bacteria due to the routine consumption of antibiotics before or after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…As lateral forces are transmitted at the contact point between the implant and abutment, the risk of loosening and screw breakage is increased by generating micromovements that induce bone remodeling [29][30][31]. In addition, the presence of gaps on the implant-abutment surface can cause microleakage and bacterial accumulation, which can compromise the dental implant success [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%